The IMDI metadata framework, its current application and future direction. (4th October 2006) - Broeder, Daan; Wittenburg, Peter
The IMDI Framework offers next to a suitable set of metadata descriptors for language resources, a set of tools and an infrastructure to use these. This paper gives an overview of all these aspects and at the end describes the intentions and hopes for ensuring the interoperability of the IMDI framework within more general ones in development. An evaluation of the current state of the IMDI Framework is presented with an analysis of the benefits and more problematic issues. Finally we describe work on issues of long-term stability for IMDI by linking up to the work done within the ISO TC37/SC4 subcommittee (TC37/SC4).